Education on the Prevention and Control of Hypertension in the Elderly in Kebitan Hamlet, Sendangarum, Minggir, Sleman, Yogyakarta - Medawati, Ana; Aziz, Azzam Bilal Abdul; Rahman, Andy; Hidayat, Ahmad Baihaqi Fanani; Abdul, Umar; Amalia, Amira Sekar; Muthmainnah, Dhea Aleyda; Handayani, Dila Gustiana; Nurhidayah, Najmah Aliyah (Indonesian Journal of Society Development, 2024)
Health problems related to age are usually accompanied by a decrease in the function of the body's organs, which can lead to various degenerative diseases, one of which is hypertension. Because hypertension is so common and associated with a higher risk of kidney disease, it is one of the most common health problems in the world. Hypertension is a type of degenerative disease. Physically, the main causes of hypertension include diabetes mellitus, heart disease, stroke, and general public health problems that are not effective in treating hypertension. In addition to being a significant risk factor for stroke, hypertension can also worsen peripheral artery disease. or often called a heart attack. The aim of this activity is to check blood pressure, provide education regarding the prevention and management of hypertension, and carry out hypertension exercises. To assess the level of understanding of residents regarding the material provided, before providing community outreach there will be a pretest, posttest at the end of the session, and training as a closing. Topics covered in the questions include steps to control, prevent, and manage hypertension